Exploration of the Risk Return Equilibrium Mechanism for ESG Portfolio Optimization: Evidence from China’s Carbon Financial Market - Li, Ai (Journal of Global Economy, Business and Finance, 2025)
This study investigates the equilibrium mechanism between risk and return in ESG portfolio optimization under the development of China’s carbon financial market. It finds that carbon finance reduces portfolio risks by incentivizing corporate ESG improvements while simultaneously offering new investment opportunities. By integrating ESG factors with carbon pricing signals, portfolios can achieve superior risk-adjusted performance. The analysis contributes to the literature by bridging carbon market mechanisms and ESG investment theory, providing new insights for investors, regulators, and policymakers.